Effect of temperature and hydrogen on palm oil cracking over MCM-41/ZSM-5 composite catalysis [electronic resource] - 237520 Siti Kartina Abdul Karim (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2006